Divalin Leuprorelin Acetate Therapy in Women with Endometriosis-Adenomyosis Tumors at The Obgyn Clinic of the Konawe Hospital BLUD: Case Report - Heni Selvia; Gita Suci Ramadanti Puanana; Resky Rahmawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study was. To identify the effectiveness of leuprorelin acetate therapy in women diagnosed with endometriosis-adenomyosis tumors. Materials and methods. This descriptive case report study was conducted from March to May 2025. The subject was a 32-year-old female patient diagnosed with endometriosis-adenomyosis tumors. The intervention consisted of divalin leuprorelin acetate injection therapy at a dose of 3.75 mg once monthly for 3 months, administered for 5-10 minutes each time. Data were collected through interviews, observation, and documentation.The focus of this study was changes in tumor size/mass before and after therapy as the primary outcome, and changes in clinical manifestations or symptoms following divalin leuprorelin acetate injection therapy as a secondary outcome. Prior to the intervention, the patient underwent a transvaginal ultrasound. This intervention involved the patient's family, who received education regarding divalin leuprorelin acetate injection therapy and its effects after administration. Result. Preliminary transvaginal ultrasound results before therapy revealed a tumor/mass in the uterus (endometriosis) measuring 5.59 cm and 4.03 cm. Furthermore, there was uterine thickening measuring 6.26 cm in length and 3.51 cm in width.However, after three months of therapy, the adenomyosis mass/tumor decreased in size, measuring 3.69 cm and 2.92 cm in length. The uterine thickening decreased to 4.6 cm in length, but not significantly in width, reaching 3.7 cm, compared to 3.51 cm before therapy. Conclusions. Divaline leuprorelin acetate therapy can reduce tumor size, reduce pain, and alleviate other symptoms. It can also improve hormone levels. This therapy can also reduce the risk and delay the need for surgery if patients adhere to treatment after being diagnosed with endometriosis/adenomyosis.